2013
DOI: 10.3892/ijo.2013.1947
|View full text |Cite
|
Sign up to set email alerts
|

Huaier aqueous extract suppresses human breast cancer cell proliferation through inhibition of estrogen receptor α signaling

Abstract: Abstract. Estrogen receptor α (ERα) has been reported to play a critical role in promoting the growth of breast tumor cells. In the present study, we explored the effect of Huaier extract on estrogen receptor α signaling in breast cancer cell lines. Our data demonstrated that Huaier extract effectively inhibited the proliferation of the MCF-7, T47D and ZR-75-1 human breast cancer cell lines. For the mechanism analysis, we demonstrated that Huaier extract significantly reduced the mRNA and protein levels of ERα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The nuclear factor κB (NF-κB) pathway, an essential pathway for tumorigenesis (28), is involved in this process. Following Huaier treatment, phosphorylated levels of p65 were reduced almost to the basal level without estrogen, suggesting that Huaier extract abolished the effect of estrogen on the activation of NF-κB and thus suppressed the proliferation of breast cancer cells induced by estrogen (27).…”
Section: Anti-proliferative Effect Of Huaiermentioning
confidence: 93%
See 1 more Smart Citation
“…The nuclear factor κB (NF-κB) pathway, an essential pathway for tumorigenesis (28), is involved in this process. Following Huaier treatment, phosphorylated levels of p65 were reduced almost to the basal level without estrogen, suggesting that Huaier extract abolished the effect of estrogen on the activation of NF-κB and thus suppressed the proliferation of breast cancer cells induced by estrogen (27).…”
Section: Anti-proliferative Effect Of Huaiermentioning
confidence: 93%
“…A recent study found that Huaier extract efficiently inhibited estrogen- stimulated proliferation in three ERα-positive breast cancer cell lines (MCF-7, T47D and ZR-75-1), confirmed by marked downregulation of ERα mRNA and protein levels in Huaiertreated cells. This process was associated with activation of the proteasome (27). The nuclear factor κB (NF-κB) pathway, an essential pathway for tumorigenesis (28), is involved in this process.…”
Section: Anti-proliferative Effect Of Huaiermentioning
confidence: 99%
“…Huaier extract has been used in China for approximately 1600 years [4]; however, its anti-tumor effects were confirmed more recently [8, 13, 41]. We have previously demonstrated that Huaier extract induces autophagy and apoptosis [4, 11, 31], regulates tumor-associated macrophages [10], inhibits cancer stem cells [12], and suppresses the ERa signaling pathway [13]. However, its underlying mechanisms were not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Xie HX et al and Zhang F et al reported that Huaier induced cell cycle arrest at the G2 phase in the gastric cancer MKN45 and SGC7901 cells and melanoma A875 cell line [15,17]. Wang X et al and Zhang N et al reported that cellcycle arrest occurs in breast cancer MCF-7 and MDA-MB-231 cells and human umbilical vein endothelial cells in the G0/G1 phase [16,31]. Zhang C found that Huaier extract induces hepatocellular carcinoma cell HepG2 and Bel-7402 arrest in S phase [32].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%